1992 IEEE MTT-S Microwave Symposium Digest 1992
DOI: 10.1109/mwsym.1992.187984
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of millimeterwave coplanar lines on gallium arsenide and indium phosphide over the range 1-60 GHz

Abstract: Extensive attenuation data of coplanar lines on semi-insulating GaAs and InP is presented over the frequency range 1-60 GHz. On-wafer measurements were used to obtain the S-Parameters. A ground-to-ground spacing of 30,60,90 and 120 mm, typical for that used in todays microwave and millimeterwave integrated circuit applications, was investigated. The center line width (impedance) and the evaporated gold metal thickness were varied. For the frequency range investigated (metal thickness less than 2-3 times the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…This data leads to a loss in the order of 0.17 dB for a line at 110 GHz (often used in higher harmonic termination). This low value of insertion loss is comparable to those achieved in III-V technologies [17], making the use of low-attenuation CPWs in silicon technology feasible over the full range of microwaves.…”
Section: A Transmission Linesmentioning
confidence: 60%
See 1 more Smart Citation
“…This data leads to a loss in the order of 0.17 dB for a line at 110 GHz (often used in higher harmonic termination). This low value of insertion loss is comparable to those achieved in III-V technologies [17], making the use of low-attenuation CPWs in silicon technology feasible over the full range of microwaves.…”
Section: A Transmission Linesmentioning
confidence: 60%
“…This, however, brings several technological issues in focus that may form bottlenecks, in particular the considerable losses in the conventional silicon substrates [6]. Currently, resistivities of at most [10][11][12][13][14][15][16][17][18][19][20] cm [low-resistivitysilicon(LRS)]arebeingused.Thiscorrespondsto conductivities that lead to considerable substrate losses and, thus, to excessive attenuation of integrated transmission lines [7] and reduced quality factors of on-chip inductors [8]. III-V-based processes have ideal substrates in that respect, but these lack other important properties such as high thermal conductivity and high and frequency-independent permittivity that qualify silicon as a true microwave substrate [7].…”
mentioning
confidence: 99%
“…As a material with mature technology, silicon is increasingly used for higher frequencies as well, both on standard silicon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) cm) as well as on high-resistivity silicon ( 1000 cm) [1], [2], [17].…”
Section: Onolithic Microwave Integrated Circuits (Mmic's)mentioning
confidence: 99%
“…Measurements [12], [13] have shown that high-resistivity silicon is nearly as good a substrate for microwave and millimeter-wave MMIC's as GaAs and InP [14].…”
Section: A Effective Permittivitymentioning
confidence: 99%
See 1 more Smart Citation